Examining the Antecedents of Green Purchase Intention - Mishra, Udgam; Kapair, Rekha (Dristikon: A Multidisciplinary Journal, 2024)
Utilising people's consumption patterns can be a practical approach to address the worsening state of nature, which has negatively affected human health and overall welfare. The present study explores customers' green purchasing intention by examining psychological aspects, including economic, emotional, and environmental value. Structural equation modelling was utilised to examine a total of 274 responses. The results indicated that economic value, emotional value, environmental consciousness and attitude significantly influence consumers' desire to make environmentally-friendly purchases. By including psychological elements such as economic value, emotional value, and the impact of environmental consciousness in the TPB model, the ability to predict intentions to embrace green products was enhanced. Consumers' inclination to take action is heightened when they perceive that their actions impact other players in the market. The findings of this study are advantageous for marketers to comprehend and target individuals who are anticipated to purchase environmentally friendly products. Analysing the correlation between environmental impact, economic value, emotional value, and green purchasing offers valuable insights to marketers in creating effective tactics that enhance consumers' inclination to buy environmentally friendly items.